(untitled) (Update Dental College Journal, 2019)
Mandibular defects may occur from maxillofacial injury, inflammatory disease, benign or malignant tumour resections and osteoradionecrosis. Mastication, speech and facial disfigurement are often severely compromised without reconstruction leading to poor quality of life. The goal of mandibular reconstruction is to restore facial form and function, repair of mandibular continuity and soft tissue reanimation. Implant insertion should be feasible to allow occlusal rehabilitation and if possible the inferior alveolar nerve function should be restored. Mandibular reconstruction principles and techniques have evolved dramatically over the years. Refinements in techniques continue to improve patient quality of life. This paper reviews short history, current techniques and few promising future endevours related to mandibular reconstruction. Update Dent. Coll. j: 2019; 9 (2): 50-54